Fatigue contributes to the strength of training stimulus - Rooney, K. J.; Herbert, R. D.; Balnave, R. J. (Medicine & Science in Sports & Exercise, 1994)
This study compared three groups: weight training with fatigue (6 RM, 6-10 sets, 3 d/wk, for six weeks); weight training with 30 sec rests between each repetition in the sets, and an inactive control group. The fatigue group increased dynamic strength (56.3%) in the elbow flexor muscles significantly more than the rest (41.2%) and control groups (19.7%). It was concluded that greater short-term strength increases are achieved when Ss are required to lift without resting. It was hypothesized that fatigue contributed to the strength-training stimulus. Implication: Strength training repetitions should be undertaken with a goal of achieving a significant fatigue state. Less than maximal application will reduce potential benefits. (Medicine and Science in Sports and Exercise, 26, 1160-1164.)